Translanguaging in International Student Teaching: Narratives of Filipino Teachers in an Indonesian Setting - Prasetya, Willy (Universitas Negeri Semarang, 2021)
Regardless of numerous studies on translanguaging, little attention has been given to its practice among pre-service teachers, particularly in the ASEAN context. To fill this gap, this article explores the experiences of three pre-service English teachers from the Philippines who were assigned to a private elementary school in Indonesia as part of a pre-service teacher exchange program. Working in a context that did not share a similar first or second language, the three teachers used English, their second language, as a lingua franca in communicating with the students. Drawing upon data from their teaching diaries, class observation, and in-depth interviews, this article reveals that using English in the classroom was challenging because English was neither the first nor the second language of their students. Three narratives from the teachers are recounted to shed some light on their use of translanguaging to bridge the communication gap. The implication of the study is also discussed.